Boyhood scenes from provincial life - Coetzee, J. M. 1940- (Viking, 1997)
Coetzee shares his boyhood north of Cape Town, South Africa, including his relationship with his parents, his first encounters with literature, his awakening of sexual desire, his growing awareness of apartheid, and his abiding love of the veld.
Keywords: Coetzee, J. M. <1940->; Geschichte 1900-2000; Geschichte 1947-1955; Écrivains sud-africains - 20e siècle - Biographies; Authors, South African -- 20th century -- Biography; Junge; Dorf; Außenseiter; Südafrika; Biografie; Fiktionale Darstellung